Al-Suyutî Dan Kontroversi Strata Ijtihâd: Telaah atas Klaim Mujtahid Mutlaq al-Suyutî dan Landasan Normatifnya - Fanani, Ahwan (ISLAMICA: Jurnal Studi Keislaman, 2008)
The 6th century of Islam witnessed the first emergence of the new class of âulama that tended to âcloseâ the gate of ijtihad. By the closure of the gate of ijtihad I do not mean that the gate of ijtihad can indeed be closed. At some point of its development, the legal system of various schools of thought of Islam has finally been established, the resultant consequence of which being that some âulama felt that ijtihad can only be done on elaborating further the views of the previous âulama and not on proposing original views on particular legal issue of Islam. Al-Suyuti emerged during the era where legal system of Islam has already been established. He claims interestingly, that he is a mujtahid mutlaq, that is, some one who has the absolute and independent authority to do ijtihad and to extrapolate rules from the legal sources of Islam. This comes as a sharp contrast to the general belief at the time that no mujtahid mutlaq may any longer emerge. Al-Suyuti wrote al-Radd to legitimize his claim; a claim that inevitably prompted a strongobjection from his fellow legalists. Although his claim was not received with enthusiasm from the public, al-Suyuti has nonetheless made a valuable contribution in the field of the study of ijtihad. His works are applauded as a great evaluation on the subject. On various occasions, al-Suyuti wrote that the Muslim intellectuals should not be satisfied with the views of the previous âulama (taqlid) and that they should instead exercise their intellectual acumen via ijtihad.